PENGARUH KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PAKAIAN MUSLIM PADA TOKO SEDIA PEUREULAK ACEH TIMUR - febi febi; T. Muana Reﬁ; Andi Tarlis (FEBI IAIN Langsa, 2019)
This study aims to determine the effect of buying interest to the decision purchasing Muslim clothes on Sedia Toko Peureulak East Aceh. The sample in this study was 96 consumers, and the analysis equipment used simple linear regression equations, partial t-test, correlation coefﬁ cient, and determination coefﬁ cient testing. Based on the research results obtained by Y = 10.018 + 0,567X, testing coefﬁ cient correlation of 0.569, testing the determination coefﬁ cient 0.324 and testing hypotheses in the obtained tcount > ttable or 6.716 > 1.985 and tsig < 5% or 0.00 < 0.05. Thus the hypothesis of allegedly effect buying interest to decision purchasing Muslim clothes in East Aceh Peureulak Sedia Toko accepted.